Supercritical Carbon Dioxide Extraction of Seed Oil from Winter Melon (Benincasa hispida) and Its Antioxidant Activity and Fatty Acid Composition - Bimakr, Mandana; Rahman, Russly; Taip, Farah Saleena; Mohd Adzahan, Noranizan; Sarker, Md. Zaidul Islam; Ganjloo, Ali (MDPI, 2013)
In the present study, supercritical carbon dioxide (SC-CO2) extraction of seed oil from winter melon (Benincasa hispida) was investigated. The effects of process variables namely pressure (150–300 bar), temperature (40–50 °C) and dynamic extraction time (60–120 min) on crude extraction yield (CEY) were studied through response surface methodology (RSM). The SC-CO2 extraction process was modified using ethanol (99.9%)as co-solvent. Perturbation plot revealed the significant effect of all process variables on the CEY. A central composite design (CCD) was used to optimize the process conditions to achieve maximum CEY. The optimum conditions were 244 bar pressure, 46 °C temperature and 97 min dynamic extraction time. Under these optimal conditions, the CEY was predicted to be 176.30 mg-extract/g-dried sample. The validation experiment results agreed with the predicted value. The antioxidant activity and fatty acid composition of crude oil obtained under optimized conditions were determined and compared with published results using Soxhlet extraction (SE) and ultrasound assisted extraction (UAE). It was found that the antioxidant activity of the extract obtained by SC-CO2 extraction was strongly higher than those obtained by SE and UAE. Identification of fatty acid composition using gas chromatography (GC) showed that all the extracts were rich in unsaturated fatty acids with the most being linoleic acid. In contrast, the amount of saturated fatty acids extracted by SE was higher than that extracted under optimized SC-CO2 extraction conditions.